Vernacular Religion in Everyday Life Expressions of Belief. - Bowman, Marion; Valk, Ülo, 1962- (London ; New York : Routledge, 2014)
Vernacular religion is religion as people experience, understand, and practice it. It shapes everyday culture and disrupts the traditional boundaries between ''official'' and ''folk'' religion. The book analyses vernacular religion in a range of Christian denominations as well as in indigenous and New Age religion from the nineteenth century to today. How these differing expressions of belief are shaped by their individual, communal and national contexts is also explored. What is revealed is the consistency of genres, the persistence of certain key issues, and how globalization in all its cult.
PART V: Theoretical Reflections and Manifestations of the Vernacular16. Belief as generic practice and vernacular theory in contemporary Estonia; 17. Some epistemic problems with a vernacular worldview; Afterword: Manifestations of the religious vernacular: Ambiguity, power, and creativity; Index
Description based upon print version of record.
Includes bibliographical references and index.
Keywords: Religions -- Case studies; Ethnology -- Religious aspects -- Case studies; Ethnology -- Religious aspects -- Case studies; Religions -- Case studies; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; Electronic books